Risk of Ischemic Stroke Among Users of the Oral Contraceptive Pill: The Melbourne Risk Factor Study (MERFS) Group - Siritho, Sasitorn; Thrift, Amanda G.; McNeil, John J.; You, Roger X.; Davis, Stephen M.; Donnan, Geoffrey A. (Stroke (1970), 2003)
Background and Purpose— Use of oral contraceptives has increased, and there is uncertainty about the stroke risk associated with their use. Our aim was to investigate this issue. Methods— Using case-control techniques, we identified consecutive women with ischemic stroke from 4 Melbourne hospitals. All patients were between 15 and 55 years of age and had no prior stroke. Neighborhood-based control subjects were individually age-matched (±5 years) and geographically matched to subject cases. A questionnaire administered to participants elicited information about prior exposure to various potential risk factors, including the oral contraceptive pill (OCP). Results— We included 234 cases and 234 controls (mean age, 42 years). Compared with noncurrent use, current use of the OCP, in doses of ≤50 μg estrogen, was not associated with an increased risk of ischemic stroke (odds ratio [OR] 1.76; 95% CI, 0.86 to 3.61; P =0.124). Factors associated with an increased risk of ischemic stroke were a history of hypertension (OR, 2.18; 95% CI, 1.22 to 3.91), transient ischemic attack (OR, 8.17; 95% CI, 1.69 to 39.6), previous myocardial infarction (OR, 5.64; 95% CI, 1.04 to 30.61), and diabetes mellitus (OR, 5.42; 95% CI, 1.42 to 20.75); family history of stroke (OR, 2.22; 95% CI, 1.12 to 4.43); and smoking >20 cigarettes per day (OR, 3.68; 95% CI, 1.22 to 11.09). Conclusions— There was no evidence for an association between ischemic stroke and use of the OCP in low doses (≤50 μg estrogen) in young Australian women. Other modifiable risk factors such as hypertension, diabetes mellitus, and smoking are important.